2008
DOI: 10.1111/j.1749-0774.2008.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Germline polymorphism of cancer susceptibility genes in gynecologic cancer

Abstract: The multifactorial process of carcinogenesis involves mutations in oncogenes, or tumor suppressor genes, as well as the influence of environmental etiological factors. Common DNA polymorphisms in low penetrance genes have emerged as genetic factors that seem to modulate an individual's susceptibility to malignancy. Genetic studies, which lead to a true association, are expected to increase understanding of the pathogenesis of each malignancy and to be a powerful tool for prevention and prognosis in the future.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…In recent years, common DNA polymorphisms in low penetrance genes emerged as genetic factors that seem to modulate an individual's susceptibility to malignancy, through interaction with environmental factors, such as diet or smoking 1 . A large number of previous studies have suggested the possible correlation between genetic polymorphisms of cancer susceptibility genes and the higher risk of human malignant tumors 2,3 . Genetic studies, which lead to a true association, are expected to increase understanding of the pathogenesis of each malignancy and to be a powerful tool of prevention and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, common DNA polymorphisms in low penetrance genes emerged as genetic factors that seem to modulate an individual's susceptibility to malignancy, through interaction with environmental factors, such as diet or smoking 1 . A large number of previous studies have suggested the possible correlation between genetic polymorphisms of cancer susceptibility genes and the higher risk of human malignant tumors 2,3 . Genetic studies, which lead to a true association, are expected to increase understanding of the pathogenesis of each malignancy and to be a powerful tool of prevention and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The p53 gene shows a polymorphism at codon 72 with a single‐base change that causes an amino acid replacement in the transactivation domain of the protein of Arg (CGC) by Pro (CCC) 7 . Although the functional differences of these two variants of p53 protein are still unclear, single nucleotide polymorphism (SNP) at codon 72 of the p53 gene has been associated in the last decade with the risk of developing various neoplasms 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…Fifty-seven were excluded for various reasons (26 studies did not involve CC, 18did not involve polymorphisms, 5 did not include controls, 4 were conducted on overlapping populations, and 4 were review articles). Finally, 23 case-control studies [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40] were included in the GSTM1 genotype meta-analysis (2343 cases and 2662 controls). The meta-analysis included studies from China, India, Japan, Korea, Italy, USA, Greece, Brazil, Turkey, and Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…B. Association found between polymorphism in immune and apoptosis-related genes and CC susceptibility [5,6,16,17,34]. C. Role of Fc␥RIIIa in inducing ADCC and apoptosis and the association of V158F with autoimmune diseases and viral infections Percentage referred to total of cases for each group.…”
Section: Discussionmentioning
confidence: 99%